Combating Algorithmic Discrimination in the Context of Dependent Employment by Utilising Article 22 of the General Data Protection Regulation - Greiner, Conrad (Central European Academy Law Review, 2025)
Employers are increasingly using algorithms to automate their decisionmaking processes. This is true not only for digital labour platforms but also for more traditional companies. By using algorithms, employers aim for faster decision-making and (as a result) a reduction in workload. Algorithms are also considered more objective than human intuition. However, algorithmic discrimination is widely documented. In many cases, anti-discrimination law is ill-equipped to protect employees from such discrimination. This study examines the extent to which Article 22 of the General Data Protection Regulation (GDPR) can be utilised to combat algorithmic discrimination in the context of dependent employment.